Powering of an HTS dipole insert-magnet operated standalone in helium gas between 5 and 85 K. (25th April 2018) - Nugteren, J van; Kirby, G; Bajas, H; Bajko, M; Ballarino, A; Bottura, L; Chiuchiolo, A; Contat, P-A; Dhallé, M; Durante, M; Fazilleau, P; Fontalva, A; et al.
Abstract: This paper describes the standalone magnet cold testing of the high temperature superconducting (HTS) magnet Feather-M2.1-2. This magnet was constructed within the European funded FP7-EUCARD2 collaboration to test a Roebel type HTS cable, and is one of the first high temperature superconducting dipole magnets in the world. The magnet was operated in forced flow helium gas with temperatures ranging between 5 and 85 K. During the tests a magnetic dipole field of 3.1 T was reached inside the aperture at a current of 6.5 kA and a temperature of 5.7 K. These values are in agreement with the self-field critical current of the used SuperOx cable assembled with Sunam tapes (low-performance batch), thereby confirming that no degradation occurred during winding, impregnation, assembly and cool-down of the magnet. The magnet was quenched many tens of times by ramping over the critical current and no degradation nor training was evident. During the tests the voltage over the coil was monitored in the microvolt range. An inductive cancellation wire was used to remove the inductive component, thereby significantly reducing noise levels. Close to the quench current, drift was detected both in temperature and voltage over the coil. This drifting happens in a time scale of minutes and is a clear indication that the magnet has reached its limit. All quenches happened approximately at the same average electric field and thus none of the quenches occurred unexpectedly.